Oxidation Behavior of the Polycrystalline Ni-Base Superalloy VDM® Alloy 780 - Kirchmayer, Andreas; Weiser, Martin; Randelzhofer, Peter; Freund, Lisa; Gehrmann, B.; Haghighat, M. Hafez; Huenert, D.; Göken, Mathias; Neumeier, Steffen (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2023)
VDM® Alloy 780 is a newly developed polycrystalline Ni-base superalloy with high contents of Co, Cr, and Al intended for operating temperatures up to 750 °C. The alloy is precipitation strengthened by the γ′ phase, which is analyzed by atom probe tomography. Additionally, δ and η phases are utilized for grain boundary pinning. It is shown that the δ and η phases precipitate either plate like or in a fine lamellar structure inside each other. VDM® Alloy 780 shows superior oxidation resistance in comparison with Udimet 720Li and A718Plus, as seen by a lower mass gain and thinner oxide layers at 800 °C and 900 °C. This superior behavior is analyzed in detail by TEM and STEM investigations of the oxide scales from which it is concluded that the Al/Ti ratio in these alloys plays an important role on the oxidation behavior.<br